Deuterium metabolic imaging – Back to the future - De Feyter, Henk M.; de Graaf, Robin A. (Journal of magnetic resonance (1997), 2021)
[Display omitted] •The promise of deuterium as a metabolic tracer was recognized soon after the discovery of chemical isotopes.•Deuterium NMR has only seen sporadic applications due to apparent downsides related to relaxation and resolution.•The short relaxation times, low natural abundance and sparsity of the spectra are advantages for in vivo deuterium NMR.•Deuterium metabolic imaging (DMI) is a robust method to map metabolism of deuterated substrates non-invasively in 3D. Deuterium metabolic spectroscopy (DMS) and imaging (DMI) have recently been described as simple and robust MR-based methods to map metabolism with high temporal and/or spatial resolution. The metabolic fate of a wide range of suitable deuterated substrates, including glucose and acetate, can be monitored with deuterium MR methods in which the favorable MR characteristics of deuterium prevent many of the complications that hamper other techniques. The short T1 relaxation times lead to good MR sensitivity, while the low natural abundance prevents the need for water or lipid suppression. The sparsity of the deuterium spectra in combination with the low resonance frequency provides relative immunity to magnetic field inhomogeneity. Taken together, these features combine into a highly robust metabolic imaging method that has strong potential to become a dominant MR research tool and a viable clinical imaging modality. This perspective reviews the history of deuterium as a metabolic tracer, the use of NMR as a detection method for deuterium in vitro and in vivo and the recent development of DMS and DMI. Following a review of the NMR characteristics and the biological effects of deuterium, the promising future of DMI is outlined.